133 Development of novel cellular therapeutics for metastatic and primary CNS malignancies. (9th November 2020) - Rennert, Paul; Birt, Alyssa; Su, Lihe; Wu, Lan; Dufort, Fay; Lobb, Roy; Ambrose, Christine; Rennert, Paul
Abstract : Background: Treatment of solid tumors with cell therapeutics will require optimal T cell persistence, fitness, and trafficking. Heterogeneous solid tumors will also have to be attacked through multiple antigens simultaneously in order to prevent resistance linked to loss of antigen expression. Here we use chimeric antigen receptor (CAR) T cells that secrete bridging proteins that act as CAR-T engagers to create an optimal platform for attacking solid tumors in the CNS. Methods: Lentiviral vectors encoding an anti-CD19 CAR and secreted bridging proteins were created. The bridging proteins contained the CD19 extracellular domain, which is the target for the CAR, and anti-tumor antigen binding domains derived from antibodies (scFv and llama VH). The resulting anti-CD19 CAR T cells secrete the bridging proteins. These candidate cell therapeutics were evaluated for antigen binding and induction of antigen-specific cytotoxicity. An anti-CD19 CAR that secretes a CD19-anti-Her2 bridging protein has moved into development. Using the CD19-anti-Her2 bridging protein as a core module, we have begun evaluating a series of multi-antigen bridging proteins. Results: CAR-CD19 T cells that secrete bridging proteins have potent cytotoxic activity against single- and multi-antigen-positive cells. ALETA-002 is the lead candidate lentiviral vector construct encoding the anti-CD19 CAR domain and the CD19-anti-Her2 bridging protein, and has entered a GMP viral particle development campaign. This therapeutic will be systemically administered to Her2-positive breast cancer patients who are relapsing with CNS metastases. Next, multi-antigen bridging proteins encoding an anti-Her2 scFv and anti-B7H3, anti-B7H6 or anti-IL13Ra2 llama VH were assayed for potency. Lead candidates for development for the treatment of primary CNS malignancies were identified and are being manufactured at pilot-scale in 4-plasmid lentivirus production runs. Conclusions: The use of anti-CD19 CAR T cells that can expand off of the normal CD19-positive B cell pool enables tumor-antigen independent persistence, fitness and robust trafficking into the CNS. The use of small, modular bridging proteins allows us to leverage anti-CD19 CAR T cells and use these to attack solid tumor antigens that are present on CNS resident cancers and on CNS metastatic lesions. Novel cell therapeutics for the treatment of Her2-positive CNS metastases and heterogeneous primary CNS malignancies including glioblastoma and the pediatric gliomas have been developed.